Interfering hsa_circ_0073748 alleviates caerulein-induced ductal cell injury in acute pancreatitis by inhibiting miR-132-3p/TRAF3/NF-κB pathway. Issue 2 (17th January 2022) - Ren, Song; Pan, Longfei; Yang, Linqing; Niu, Zequn; Wang, Liming; Gao, Yanxia; Liu, Jie; Liu, Zhong; Pei, Honghong
ABSTRACT: Circular RNA hsa_circ_0073748 (circ_0073748) is upregulated in patients with acute pancreatitis (AP), a clinically common sudden inflammatory response. MicroRNA (miR)-132-3p is a stress-induced factor with high conservation between species. Herein, expression and role of circ_0073748 and miR-132-3p in caerulein-induced pancreatitis were studied. Expression levels of circ_0073748, miR-132-3p, TNF receptor associated factor 3 (TRAF3), Bcl-2 and Bcl-2-associated X protein (Bax) were examined by reverse transcription-quantitative PCR and Western blotting. Cell proliferation was measured by MTS and EdU assays. Flow cytometry and assay kits detected apoptosis, inflammatory, and oxidative responses. Western blotting detected nuclear factor (NF)-κB signaling pathway. Circ_0073748 was upregulated and miR-132-3p was downregulated in AP patients' plasma and human pancreatic ductal HPDE6-C7 cells with caerulein induction. Interfering circ_0073748 and reinforcing miR-132-3p improved cell viability, EdU incorporation, and superoxide dismutase (SOD) activity of caerulein-treated HPDE6-C7 cells but suppressed malonaldehyde (MDA), IL-6 and TNF-α levels and apoptosis rate. Moreover, TRAF3 downregulation was allied with circ_0073748 silencing and miR-132-3p overexpression in caerulein-induced HPDE6-C7 cells. Mechanically, circ_0073748 was identified as a sponge for miR-132-3p to modulate TRAF3 expression, thus establishing a competitive endogenous RNA (ceRNA) regulation model. Notably, circ_0073748 blockage could suppress expressions of phosphorylated P65 (p-P65) and p-IκB in caerulein-induced HPDE6-C7 cells by promoting miR-132-3p and inhibiting TRAF3. Silencing circ_0073748 and upregulating miR-132-3p could alleviate caerulein-induced HPDE6-C7 injury and inactivate canonical NF-κB signal by inhibiting TRAF3. Circ_0073748/miR-132-3p/TRAF3 ceRNA pathway might be one underlying mechanism and therapeutic target of caerulein-induced AP.